Health care workers' knowledge and perceptions on WHO hand hygiene guidelines, and the perceived barriers to compliance with hand hygiene in Cyprus - Despo Constantinou; Ioannis Leontiou; Meropi Mpouzika; Koralia Michail; Nikos Middletton; Anastasios Merkouris (BMC, 2024)
Abstract Background Hand hygiene (HH) is recognized as an important measure to avoid the transmission of harmful germs, and assists significantly in preventing healthcare-associated infections. HH compliance among health care workers (HCWs) is a result of their knowledge and perceptions. Aim To investigate the knowledge and perceptions of WHO hand hygiene guidelines among HCWs, and the perceived barriers to compliance with hand hygiene in a major public hospital in Cyprus. Methods A descriptive correlational study was conducted in September of 2019. The target population was all of the HCWs in Nicosia General Hospital (N = 1,386). The final sample consisted of 820 participants (119 physicians, 613 nurses, 27 physiotherapists, 59 ward assistants, 2 unidentified). This study used the HH knowledge and perception questionnaire that was developed by the WHO. Results The results revealed that the average percentage score for knowledge among our sample was 61%, and statistically significant differences were observed among HCWs with regard to certain questions. It was found that HCWs, in most of their responses, presented high percentages of correct answers regarding their perceptions on hand hygiene guidelines but several perceived barriers to compliance on HH guidelines were identified as well. Conclusions Knowledge and perceptions of HH guidelines among HCWs were moderate and good respectively. In addition, several perceived barriers to compliance on HH recommendations were identified. HH education is recognized as an important tool for removing these barriers but the recommended HH strategy should be multi-modal and consider local resources, administrative support and barriers to compliance with HH.